2001
DOI: 10.1046/j.1525-1470.2001.1862005.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Piebaldism and Neurofibromatosis Type 1 in a Girl

Abstract: We report an 11-year-old girl with both piebaldism and neurofibromatosis type 1 (NF1). The patient had large depigmented patches on her lower limbs and a white forelock since birth. In addition, some café au lait spots were present on her trunk at birth and had increased in number and size during childhood in concomitance with the appearance of axillary and inguinal freckling. Neither neurofibromas nor Lisch nodules were detected and the patient was otherwise healthy. Pedigree analysis revealed inheritance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…At least four cases of piebaldism associated with neurofibromatosis have been reported and none of them developed neurofibromas, although at their young age (3-17 years of age) it is not possible to exclude the possibility of subsequent development of those lesions [8]. Whether, the simultaneous occurrence of these two dominantly inherited diseases is significantly higher than by chance remains to be established [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least four cases of piebaldism associated with neurofibromatosis have been reported and none of them developed neurofibromas, although at their young age (3-17 years of age) it is not possible to exclude the possibility of subsequent development of those lesions [8]. Whether, the simultaneous occurrence of these two dominantly inherited diseases is significantly higher than by chance remains to be established [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in understanding the molecular basis, the diagnosis of NF1 is based on clinical criteria established by the National Institute of Health (NIH) Consensus Conference in 1987 [8]. According to these criteria, two or more of the following findings establish the diagnosis of NF1: a) six or more café-au-lait spots greater than 5 mm in diameter in prepubertal individuals and more than 15 mm after puberty, b) two or more neurofibromas or one plexiform neurofibroma, c) freckling in the axilary or inguinal regions, d) optic pathway tumor, e) two or more Lisch nodules (iris hamartomas), f) distinctive bone lesions such as sphenoid wing dysplasia and g) a first-degree relative with NF1 [7][8][9].…”
Section: Introduction To Piebaldismmentioning
confidence: 99%
“…However, Schwann cell progenitors persist or Schwann cells dedifferentiate into progenitor-like cells in neurofibromas in NF1 [16]. Much evidence indicated that the loss of the Nf1 gene in NF1 plays an important role in the initiation of tumorigenesis of neurofibromas and that all of the known NF1 phenotypes result from the inheritance or appearance of a mutant allele of the Nf1 gene [17]. The Nf1 gene product, neurofibromin, functions as a GTPase activation protein (GAP), a negative regulator of the cellular Ras kinase [18].…”
Section: ………………………………………………………………………………mentioning
confidence: 99%
“…Most patients are otherwise healthy and have no systemic symptoms, but piebaldism may rarely be associated with other disorders such as Hirschsprung's disease, neuro fi bromatosis type 1, Grover's disease, and deafness [64][65][66][67] . Also, because the depigmentation of piebaldism is striking in dark-skinned races, there is signi fi cant emotional burden.…”
Section: Piebaldismmentioning
confidence: 99%